Therapeutic drug monitoring in drug overdose - Dawson, Andrew H (Blackwell Science Inc, 2001)
The treatment of poisoned patients is still largely defined by history, clinical assessment and interpretation of ancillary investigations. Measurement of drug concentrations is clinically important for relatively few compounds. Most measurements form an adjunct to and should not be considered a substitute for clinical assessment. Drug concentrations are particularly important for those compounds where the concentration is predictive of serious toxicity in an otherwise asymptomatic patient.